Diseminasi Potensi Objek Wisata di Nagari Sumpu Berbasis Webgis Menggunakan StoryMaps - Cut Zahira Rifani Kamza; Agnes Tiodora Sinaga; Marcelina Hutapea; Rexsi Kristina Sihombing; Muhammad Farouq Ghazali Matondang (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to describe the tourism potential of Nagari Sumpur, West Sumatra, and to develop a dissemination medium using WebGIS based on ArcGIS StoryMaps. The background of the research stems from the limited digital promotion of local tourism destinations that possess rich historical, cultural, and natural value. A qualitative approach was employed, involving observation, interviews, documentation, and the construction of interactive narratives on a digital platform. The results show that Nagari Sumpur holds significant tourism potential, including traditional rumah gadang houses as Minangkabau cultural heritage, the daily activities of local fishermen at Lake Singkarak, and a variety of traditional culinary offerings. The dissemination of information through StoryMaps proved effective in presenting tourism narratives in an engaging and informative way. Interactive maps, multimedia content, and ease of access were key strengths of this medium in reaching wider audiences. The implications of this research indicate that integrating geospatial technology with local cultural narratives can serve as an innovative and sustainable tourism promotion strategy, while directly empowering local communities.